Microbial Treatment and Oxidative Stress in Agricultural Plants - Irina S. Milentyeva; Natalya V. Fotina; Maria Yu. Zharko; Larisa A. Proskuryakova (Техника и технология пищевых производств)
Anthropogenic factors expose agricultural plants to abiotic and biotic stresses, one of which is oxidative stress. Oxidative stress changes cell metabolism, as well as inhibits plant growth and development. Microbial treatment is an environmentally safe method of oxidative stress prevention. The research objective was to study the antioxidant activity of microflora native to coal dumps in order to combat the oxidative stress in crops. The study featured microorganisms isolated from technogenically disturbed soils. Pure bacterial cultures were isolated by deep inoculation on beef-extract agar. A set of experiments made it possible to define the cultural, morphological, and biochemical properties of cell walls. The antioxidant activity and the amount of indole-3-acetic acid were determined on a spectrophotometer using the ABTS reagent and the Salkowski reagent, respectively. The isolated microorganisms were identified on a Vitek 2 Compact device. The biocompatibility of strains was tested by dripping, while the increase in biomass was measured using a spectrophotometer. The study revealed ten microbial strains with antioxidant activity ranging from 67.21 ± 3.08 to 91.05 ± 4.17%. The amount of indole-3-acetic acid varied from 8.91 ± 0.32 to 15.24 ± 0.69 mg/mL. The list of microorganisms included Klebsiella oxytoca, Enterobacter aerogenes, Pseudomonas putida, and Bacillus megaterium. The consortium of P. putida and E. aerogenes demonstrated the best results in antioxidant activity, indole-3-acetic acid, and biomass. Its ratio was 2:1 (94.53 ± 4.28%; 15.23 ± 0.56 mg/mL), while the optical density was 0.51 ± 0.02. Extra 2% glycine increased the antioxidant activity by 2.34%, compared to the control. Extra 0.5% L-tryptophan increased the amount of indole-3-acetic acid by 3.12 mg/mL and the antioxidant activity by 2.88%. The research proved the antioxidant activity of strains isolated from microflora native to coal dumps. The consortium of P. putida and E. aerogenes (2:1) demonstrated the best results. Further research will define its ability to reduce oxidative stress in plants.